Management of acute aortic occlusion in the setting of necrotizing pancreatitis with covered endovascular reconstruction of the aortic bifurcation - Eastan Marleau, MD; Thekla Bacharach, MD; Anand Dayama, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Acute aortic occlusion represents a rare, life-threatening condition associated with significant morbidity and mortality. Here, we present a case of acute aortic occlusion in the setting of necrotizing pancreatitis, successfully managed with covered endovascular reconstruction of the aortic bifurcation. Traditionally, treatment options for acute aortic occlusion have included thromboembolectomy, aortobifemoral bypass, and axillary bifemoral bypass. Our report demonstrates covered endovascular reconstruction of the aortic bifurcation as a viable in-line treatment option for acute aortic occlusion, particularly in patients with challenging concomitant abdominal pathology.